α-Methylated Polyamines as Potential Drugs and Experimental Tools in Enzymology - Tuomo A. Keinanen; Aki Jarvinen; Anne Uimari; Jouko Vepsalainen; Alex R. Khomutov; Nikolay A. Grigorenko; Mervi T. Hyvonen; Marc Cerrada-Gimenez; Leena Alhonen; Juhani Janne (Mini Reviews in Medicinal Chemistry, 2007)
We describe synthesis of α-methylated analogues of the natural polyamines and their use as tools in unraveling polyamine functions. Experiments with α-methylated spermidine and spermine revealed that the polyamines are exchangeable in supporting cellular growth. Degradation of the analogues by polyamine oxidase disclosed hidden, aldehydeguided stereospecificity of the enzyme.
Keywords: liver regeneration